Komunikasi Transformatif di Pesantren: Upaya Menumbuhkan Motivasi Santri Melanjutkan Studi ke Perguruan Tinggi - Kanzulfikar, Achmad; Adhi Pratama, Hayiz Historia; Tantowi, Lisy (Universitas 17 Agustus 1945 Surabaya, 2026)
Education is an important aspect of modern society because it is considered capable of increasing the level of modernity of a group. Education has significant potential in shaping a child’s attitudes and behavior, as well as in preparing individuals to assume future social roles. Furthermore, education is also needed to make people more religious and to equip them with the moral foundations required for social life. Therefore, this study aims to examine the process of transformative communication at Pondok Pesantren Al Chikmatul Mubalighoh Wa Tahfidzul Qur’an in encouraging students’ motivation to continue their studies to higher education. Using a qualitative approach with in-depth interviews, observation, and document analysis, this study finds that students’ aspirations for higher education are formed through a series of interconnected communication processes. Advice and guidance from the kyai and ustadz/ustadzah function as initial triggers that build students’ awareness of the importance of further education. Dialogical interactions in both learning activities and informal conversations strengthen students’ interpretations of higher education opportunities and shape the belief that higher education is accessible. The pesantren’s social capital—including trust, environmental support, and alumni networks—acts as a reinforcing factor that stabilizes this motivation. In addition, socialization from Sultan Ageng Tirtayasa University provides concrete information about admission pathways and scholarships, thereby clarifying students’ educational choices. This study concludes that transformative communication in pesantren not only shapes religious understanding but also contributes to the formation of students’ educational orientation and social mobility. Keywords: Transformative Communication, Pesantren (Islamic Boarding School), Higher Education Aspirations, Social Capital, Students’ Motivation.